Scrum in Practice: City Reconstruction as a Pedagogical Game Challenge - Masson, Eloisa Toffano Seidel; Calazans, Angelica Toffano S.; Bandeira, Ian Nery; Silva, Geovana Ramos Sousa; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
This paper presents an experience report on the dynamics of the Scrum Game Challenge through the customization of LEGO4Scrum. The game’s objective is to teach Scrum concepts through the simulation of the reconstruction of a city of Mariana, Minas Gerais, exploring the use of Scrum and experimenting with tools used by the software industry. As a result, we present the customizations performed, as well as the students’ and teachers’ perceptions of the advantages and disadvantages of applying the practice of the dynamic in the classroom. Our findings reveal that most students felt that the concepts covered in the dynamics could be applied during their professional practice as software developers in the industry. Moreover, the dynamic allowed them to understand how the application of Scrum works during the software development process in a clear, easy, and fun way. The students and teachers also stated that besides theoretical knowledge, it is essential to consider practical knowledge about the application of agile software development methodologies during Computer Science coursework.